The Comparison of Defaults in Credit Agreements by Customers of Conventional Banks and Islamic Banks - Ruselia, Mawar; Hafidz, Jawade (Jurnal Konstatering, 2022)
The banking industry has a very important role in the rotation of the economy. Banks as economic drivers with government assistance, provide credit facilities for the community and need each other to carry out the circulation of money in Indonesia, in which banks provide credit to the community, as well as the community is assisted financially in the form of credit capital obtained from banks. However, from the symbiosis of mutualism that exists, there are still many problems between banks and their customers related to defaults on credit agreements in both conventional banks and Islamic banks, especially conventional banks and Islamic banks in the city of Kendari, Southeast Sulawesi Province. This research method uses normative legal research, with a comparative legal approach, and the statutory regulatory approach. The results of this study areSettlement of credit agreement default disputes at conventional banks and Islamic banks consists of two ways, both litigation and non-litigation, in which the settlement of litigation disputes on conventional banks is resolved in the District Court while Islamic banks are resolved in the Religious Courts. Likewise, non-litigation dispute resolution at both conventional banks and Islamic banks has the same method with different applications starting from coaching, resheduling, reconditioning, restructuring, to confiscating assets which these two banks have different applications.Keywords : Agreement; Bank; Credit; Comparison.